Organizational Performance in Batam’s Food Industry: The Mediating Role of Organizational Culture - Edvan Suwandi; Agustinus Setyawan (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to see how organizational innovation, transformational leadership, and organizational change affect organizational performance with the mediating effect of organizational culture. Until now, the previous literature that analyzed this matter is still very minimal and the discussion of organizational performance, organizational innovation, transformational leadership, organizational change, and organizational culture variables in previous journals is still lacking in detail.  This study used cross-sectional data and a quantitative approach. Sampling is carried out by distributing questionnaires to employees of Roti Garuda Kencana Ltd and testing the hypothesis using the SPSS application. The results showed that organizational innovation, transformational leadership, and organizational change affect organizational performance. Then organizational innovation and organizational change affect organizational culture, while transformational leadership does not affect organizational culture. After that, organizational innovation, transformational leadership, and organizational change affect organizational performance through organizational culture.  Companies can make this research as an assessment and discuss research findings and how to apply them in improving organizational performance. The company is expected to engage relevant stakeholders in discussing how research findings can be integrated into the company's strategy and policies.